Cell‐Mediated Biointerfacial Phenolic Assembly for Probiotic Nano Encapsulation. (22nd March 2022) - Centurion, Franco; Merhebi, Salma; Baharfar, Mahroo; Abbasi, Roozbeh; Zhang, Chengchen; Mousavi, Maedehsadat; Xie, Wanjie; Yang, Jiong; Cao, Zhenbang; Allioux, Francois‐Marie; Harm, Gregory F. S.; Biazik, Joanna; et al.
Abstract: The use of cell‐mediated chemistry is an emerging strategy that exploits the metabolic processes of living cells to develop biomimetic materials with advanced functionalities and enhanced biocompatibility. Here, a concept of a cell‐mediated catalytic process for forming protective nano‐shells on individual probiotic cells is demonstrated. This process is leveraged by the cell environment to induce oxidative polymerization of phenolic compounds, and simultaneously these phenolic polymers assemble to form nano‐coatings around individual cell surfaces. The detailed analysis reveals that the oxidation process is triggered by an essential nutrient (manganese) of the probiotic cells, which significantly increases the oxidation rate of phenolic compounds. The phenolic coatings, encapsulating each cell in nanometre scale, demonstrate excellent biocompatibility and biodegradability. Additionally, the in situ encapsulated probiotic cells display an improved gastric tolerance of up to ≈1.4 times higher than the native cells and enhanced adhesion as high as ≈1.6 times onto a model of intestinal epithelial cells. Finally, the coated probiotic cells exhibit a high antioxidant activity as an advanced feature. Overall, this method provides a unique approach to improve the probiotic delivery using the cell machinery to engineer encapsulating nanocoatings with protective benefits and new functionalities. Abstract : Cell‐induced oxidation and assembly of phenolic compounds by probiotic cells allow in situ cytoprotective nanocoating formation on individual probiotic cells, featuring remarkable gastric resistance and tissue adhesion to intestinal cells, and antioxidant properties as an advanced function.